A REVERSE ENGINEERING APPROACH FOR THE PRODUCTS DEVELOPMENT - Marius Baban; Calin Florin Baban; Traian Buidos; Iulian Stanasel (Nonconventional Technologies Review, 2015)
Recent technological developments have made easier the application of reverse engineering. In this paper, a reverse engineering approach for the development of the products has been presented. This approach has been based on the scanning of the initial product, followed by the redesign of the initial product, the manufacturing of the redesigned product through a 3D printer and the quality inspection of the redesigned product. A system for the using of a such approach has been depicted and a case study illustrates the application of the reverse engineering approach.